Development of medication errors reporting system: an object-oriented approach. (2017) - Merhi, Mohammad I.; Patel, Sheel; Nguyen, Kevin
Medication errors pose a serious threat in the healthcare industry. This paper aims at developing a medication error reporting system (MERS) that enables medical professionals to anonymously report medication errors by opening a case in the MERS database. The object-oriented approach was used to analyse and design the MERS system. The systems requirements are first gathered with the use of questionnaires and interviews with practitioners; then, analysed based on unified modelling language techniques such as use case, class, and sequence diagrams. Implementing a MERS into hospitals allows medical professionals to analyse error patterns by referencing archived cases in the database; thus enhancing clinical practices that prevent future errors.